A new species and new record of Tyloperla (Plecoptera: Perlidae) from China - Li, Weihai; Kong, Fanbin (Zootaxa, 2020)
One new species of the genus Tyloperla Sivec & Stark, 1988, T. bimaculata sp. nov., is described from Guizhou Province of southern China. The relationships of taxonomic characteristics of T. bimaculata sp. nov. and the related species of the genus are discussed. A new species record, T. illiesi Stark & Sivec, 2005 is added to the stonefly fauna of China for the first time.